DNA immunization with in silico predicted T-cell epitopes protects against lethal SARS-CoV-2 infection in K18-hACE2 mice - Persson, Gry; Restori, Katherine H.; Emdrup, Julie Hincheli; Schussek, Sophie; Klausen, Michael Schantz; Nicol, McKayla J.; Katkere, Bhuvana; Rønø, Birgitte; Kirimanjeswara, Girish; Sørensen, Anders Bundgaard (Frontiers in Immunology, 2023)
The global SARS-CoV-2 pandemic caused significant global disruption, both socially and economically, despite highly effective vaccines being developed at an unprecedented speed. As the first licensed vaccines only target single B-cell antigens, antigenic drift could lead to loss of efficacy against emerging SARS-CoV-2 variants. Improvement of the B-cell vaccines by including multiple T-cell epitopes could potentially solve this challenge. Here we show that in silico predicted MHC class I/II ligands induced robust T-cell responses and protected against severe disease in genetically modified K18-hACE2/BL6 mice susceptible to SARS-CoV-2 infection.